Superfast assembly and synthesis of gold nanostructures using nanosecond low-temperature compression via magnetic pulsed power - Binsong Li (Nature Portfolio, 2017)
Gold nanostructures have shape-dependent properties, making synthetic control over their morphology critical. Here, the authors use dynamic compression to obtain a variety of gold nanoarchitectures, which are formed at very fast timescales by the controlled coalescence of spherical particle arrays.